Analysis of The Nature of Science in The Prototype Curriculum Based on Social and Science Students’ Book for Fourth Grade Phase B - Pratiwi, Dini Aulia; Sopandi, Wahyu; Pangesty, Desy Ayu Ratna (Postgraduate, University of Mataram, 2023)
The Nature of Science or NOS is knowledge that explains how science works and how scientists conduct research. NOS has aspects of form, namely products, processes and properties. The preparation stage, such as reviewing the literature on the NOS aspect and determining the NOS aspect used, namely from the form aspect, including products, processes, attitudes, and from the nature aspect, in the form of empirical, tentative methods, subjective, creative, theoretical and legal, socio-cultural, and scientific; The analysis stage, by analyzing the basic competencies and content in the curriculum and its embodiment in student books. This research was carried out with the following steps: Based on the results of the researchers' agreement, the minimum value limit in the data analysis process is 80%. Based on the results of the analysis, it is shown that the aspects and embodiments of the nature of science and the nature of the science books for fourth grade students are not explicitly explained. The excellent category is in the product aspect with an average percentage of >80%. While other aspects have a very less category with a percentage of <80%, even some aspects have an average percentage of <1%.